The Right to Know: Lecture by His Royal Highness Sultan Azlan Shah Sultan of Perak - Sultan of Perak, HRH Sultan Azlan Shah (Journal of Malaysian and Comparative Law, 1986)
Public Lecture on the Right to Know, delivered at the University of Science, Malaysia on 19th December 1986.